Birth Weight and Adult Bone Metabolism Are Unrelated: Results From Birth Weight–Discordant Monozygotic Twins. (December 2013) - Frost, Morten; Petersen, Inge; Andersen, Thomas L; Langdahl, Bente L; Buhl, Thora; Christiansen, Lene; Brixen, Kim; Christensen, Kaare
ABSTRACT Low birth weight (BW) has been associated with poor bone health in adulthood. The aim of this study was to investigate the association between BW and bone mass and metabolism in adult BW‐discordant monozygotic (MZ) twins. A total of 153 BW–extremely discordant MZ twin pairs were recruited from the Danish Twin Registry. Serum vitamin D (25‐hydroxyvitamin D [25OHD]) and bone turnover markers (BTMs) amino‐terminal propeptide of type I procollagen (P1NP), pyridinoline cross‐linked carboxyterminal telopeptide of type I collagen (1CTP), and cross‐linked C‐telopeptide (CTX) were quantified. Femoral neck (FN), total hip (TH), lumbar spine (LS), and whole‐body (WB) bone mineral density (BMD) (ie, FN‐BMD, TH‐BMD, LS‐BMD, and WB‐BMD, respectively) were measured using dual‐energy X‐ray absorptiometry (DXA). Twins were studied as single individuals using regression analyses with or without adjustment for height, weight, age, sex, and intrapair correlation. Within‐pair differences were assessed using Student's t test and fixed‐regression models. BW was not associated with BTMs, LS‐BMD, TH‐BMD, FN‐BMD, or WB‐BMD, but BW was associated with WB‐BMC, and WB‐Area after adjustments. Compared to the co‐twin, twins with the highest BW were heavier and taller in adulthood (mean differences ± SD): 3.0 ± 10.5 kg; 1.6 ± 2.6 cm; both p < 0.001). Within‐pair analyses showed that LS‐BMD, TH‐BMD, and FN‐BMD tended to be higher in twins with highest BW (for all: mean difference 0.01 ± 0.1 g/cm2; p = 0.08, 0.05, and 0.10, respectively). No difference was observed after adjustment for adult body size. Intrapair differences in BW were not associated with differences in any of the biochemical parameters or BMD. Small differences between twins in BMD were explained by dissimilarities in body size. These results suggest that BW and adult bone metabolism are unrelated. © 2013 American Society for Bone and Mineral Research.